Clinicians’ perception of virtual reality therapy in treating patients with obsessive compulsive disorder: a preliminary study - Eusoff Fitri Sarnin; Shalisah Sharip; Idayu Badilla Idris; Syahnaz Mohd Hashim (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
In the Western context, virtual reality (VR)-based treatments had been suggested as an intervention for anxiety disorder. Despite its potential efficacy, there is a lack of study which using VR as an intervention, especially for obsessive-compulsive disorder (OCD) in Asian countries. Therefore, the present study aimed to examine what elements are required to design VR and the suitability of VR as an intervention in OCD for the local context. To address this, six clinicians, consisting of three clinical psychologists and three psychiatrists, were interviewed. They were interviewed using a semi-structured interview protocol related to their perception on VR as an intervention for OCD patients, as well as the cognitive behaviour therapy (CBT) elements that can be incorporated in VR. The findings showed that all clinicians anonymously supported CBT to be augmented into VR as part of intervention for OCD to overcome logistics issues, the interactive nature of the virtual environment and the sense of presence similar to a real-life situation. The side effects of VR also need to be studied before employing these new interventions. In conclusion, VR can be used as an intervention for OCD. CBT-VR intervention can be applied in the Asian context by using similar CBT modules which should be modified according to cultural context.